MRSA compendium of epidemiology, transmission, pathophysiology, treatment, and prevention within one health framework - Shoaib, Muhammad; Aqib, Amjad Islam; Muzammil, Iqra; Majeed, Noreen; Bhutta, Zeeshan Ahmad; Kulyar, Muhammad Fakhar-e-Alam; Fatima, Mahreen; Zaheer, C-Neen Fatima; Muneer, Afshan; Murtaza, Maheen; Kashif, Muhammad; Shafqat, Furqan; et al. (Frontiers in Microbiology, 2023)
Staphylococcus aureus is recognized as commensal as well as opportunistic pathogen of humans and animals. Methicillin resistant strain of S. aureus (MRSA) has emerged as a major pathogen in hospitals, community and veterinary settings that compromises the public health and livestock production. MRSA basically emerged from MSSA after acquiring SCCmec element through gene transfer containing mecA gene responsible for encoding PBP-2α. This protein renders the MRSA resistant to most of the β-lactam antibiotics. Due to the continuous increasing prevalence and transmission of MRSA in hospitals, community and veterinary settings posing a major threat to public health. Furthermore, high pathogenicity of MRSA due to a number of virulence factors produced by S. aureus along with antibiotic resistance help to breach the immunity of host and responsible for causing severe infections in humans and animals. The clinical manifestations of MRSA consist of skin and soft tissues infection to bacteremia, septicemia, toxic shock, and scalded skin syndrome. Moreover, due to the increasing resistance of MRSA to number of antibiotics, there is need to approach alternatives ways to overcome economic as well as human losses. This review is going to discuss various aspects of MRSA starting from emergence, transmission, epidemiology, pathophysiology, disease patterns in hosts, novel treatment, and control strategies.